Al-Harakaḧ al-Jawhariyaḧ as Perfecting of Existence and Its Relation With Natural Sciences and Humanities - Rahmat Effendi (Jurnal Ushuluddin, 2021)
Mullā Ṣadrā’s discourse in the discourse of Islamic philosophy is only limited to ontological and epistemological aspects. There has not been much further investigation into Ṣadrā’s philosophy. This causes Ṣadrā’s philosophy to dwell only in the theoreticalmetaphysical realm. If we look further, Ṣadrā’s philosophy also has a relationship with the natural sciences and the humanities. Through the concept of al-harakaḧ al-jawhariyaḧ Ṣadrā explains this. Al-Harakaḧ al-jawhariyaḧ as the embodiment of the principle of existence (aṣālaḧ al-wujūd) is not only Ṣadrā’s ontology but as Islamic original thought in solving ontological problems since ancient times. Al-Harakaḧ al-jawhariyaḧ or substance motion is an immaterial gradual motion in every existenceentity, both material and non-material existence. Each mawjūd entity is an existence that experiences motion to point to one point, namely perfection. This perfection is in an immaterial state in every hierarchical reality of existence. Every existence, both human and natural, will move towards this essential perfection. This article will reveal that alharakaḧ al-jawhariyaḧ is a motion in the context of improvement in terms of substance and accident. It is also through this concept that Ṣadrā shows his relation to the natural sciences and humanities. This relationship is in the form of proving the existence of God, the creation of nature, and the social relations of society. This research is based on library research with a descriptive analysis method and holistic approach. In the end, al-harakaḧ al-jawhariyaḧ has a broad relationship in existence and all existing entities